The Role of Helicobacter pylori Seropositivity in Insulin Sensitivity, Beta Cell Function, and Abnormal Glucose Tolerance - Lou Rose Malamug; Rudruidee Karnchanasorn; Raynald Samoa; Ken C. Chiu (Scientifica, 2014)
Infection, for example, Helicobacter pylori (H. pylori), has been thought to play a role in the pathogenesis of type 2 diabetes mellitus (T2DM). Our aim was to determine the role of H. pylori infection in glucose metabolism in an American cohort. We examined data from 4,136 non-Hispanic white (NHW), non-Hispanic black (NHB), and Mexican Americans (MA) aged 18 and over from the NHANES 1999-2000 cohort. We calculated the odds ratios for states of glucose tolerance based on the H. pylori status. We calculated and compared homeostatic model assessment insulin resistance (HOMA-IR) and beta cell function (HOMA-B) in subjects without diabetes based on the H. pylori status. The results were adjusted for age, body mass index (BMI), poverty index, education, alcohol consumption, tobacco use, and physical activity. The H. pylori status was not a risk factor for abnormal glucose tolerance. After adjustment for age and BMI and also adjustment for all covariates, no difference was found in either HOMA-IR or HOMA-B in all ethnic and gender groups except for a marginally significant difference in HOMA-IR in NHB females. H. pylori infection was not a risk factor for abnormal glucose tolerance, nor plays a major role in insulin resistance or beta cell dysfunction.